Training on Environmental Poster Design Based on Physics Data by Vocational High School Students as Agents of Change - Nasution, Hanifah Nur; Zainy, Ahmad; Lubis, Roy Mirdan; Hidayat, Thofik; Nasution, Sari Wahyuni Rozi; Fauzi, Rahmad (Jurnal IPTEK Bagi Masyarakat, 2025)
Environmental issues such as global warming, air pollution, and climate change require the active participation of all levels of society, including the younger generation. Vocational high school students, as future skilled workers, have great potential to become agents of change through relevant skills in their field. This community service activity aims to enhance the understanding and awareness of students at SMK Negeri 1 Portibi regarding environmental issues through training in environmental poster design based on environmental physics data. The method used is a project-based learning approach, consisting of introducing environmental physics concepts, collecting field data (temperature, humidity, and light intensity), conducting simple analysis, and creating digital posters using graphic design software such as Canva and CorelDraw. The activity was attended by students from various departments, with a participation rate of more than 90% completing the entire training series. The results show a significant improvement in students’ understanding of environmental physics concepts as well as their graphic design skills. The produced posters are not only informative but also communicative and visually appealing, making them effective as environmental campaign media in schools. This activity demonstrates that integrating science and art can be an innovative educational strategy to encourage students’ roles as agents of change in preserving the environment.